Utility of PCDTBT polymer for the superior sensing parameters of electrical response based relative humidity sensor - Zafar, Q.; Sulaiman, K. (Elsevier, 2016)
In the present study, organic polymer PCDTBT has been deposited on pair of planar aluminium (Al) electrodes to construct an integrated capacitive and impedance type humidity sensor (Al/PCDTBT/Al). The solution processable organic polymer has been deposited through a facile spin coating technique. The structural characterization and surface morphology study of active layer has been performed by XRD and AFM. The humidity sensing characteristics of the sensor have been investigated by exposing the organic active layer to various wide range relative humidity (%RH) levels (15-98%RH) at room temperature. The proposed sensor exhibits significantly higher sensitivity ~ 39.73 pF/%RH and 821.81 kΩ/%RH when operated in capacitive and impedance mode, respectively. In addition, the capacitive sensor has desirable reproducibility, narrow hysteresis (~ 5%), fast response (8 s) and reset (14 s) time. Significantly improved sensing parameters suggest that the proposed sensor may be implemented meritoriously for continuous humidity assessment in environment.